A study on the relationship between inflation rate, interest rate and gross domestic product towards Industrial Production Index / Mohd Radzi Mohd Ridza (Faculty of Business and Management, 2006)
This study is conducted to answer the question whether the inflation rates which refer to Consumer Price Index (CPI), the interest rates which refer to Base Lending Rate (BLR) and Gross Domestic Product (GDP) can affect the Industrial Production Index (DPI) in Malaysia, With that, interest rates, inflation rates and gross domestic product will be put as independent variables and IPI will be as the dependent variable. The study focuses on economic growth that has been recorded in ten years from 1996 to 2005. Multiple Linear Regression analysis is used in finding out the relationship between dependent and independent variables. Based on the analysis, it shows that there is no significant relationship arise between inflation (CPI) and Industrial Production Index (IPI). It is also concluded that there is a significant relationship between interest rate (BLR) and Gross domestic product (GDP) with the IPI. The IPI react negatively with the changes in interest rates and react positively towards the changes in GDP.